„Stary człowiek zostaje zapomniany”. O procesie przebudowy pamięci zbiorowej w repertuarze Pieśni Ziemi Izraela - Jeż, Agnieszka (Res Facta Nova, 2025)
In this article, I discuss issues related to the manipulation of memory and deliberate forgetting, which were elements of the process of creating an invented tradition in the Zionist Jewish community of the first half of the 20th century. The titular Songs of the Land of Israel [Hebrew: Shirei Eretz Israel] is a vocal repertoire accompanying the first aliyahs to Palestine, building a new identity for its future inhabitants and preparing the ideological ground for the construction of a Jewish National Home (and later also the State of Israel). Conceived as “new folk songs”, their primary task was to integrate the culturally extremely diverse Jewish community, and, no less importantly, to attest to the right of Jews to live in the Land of Israel. By their creators and ideologists, the newly created songs in Hebrew were understood as a tool for shaping identity, and the memory of the nation’s history, which was to be expressed in them, was treated instrumentally, both in the textual layer and in the music. It is interesting to trace the suppression of certain threads present in diasporic Jewish cultures, replacing them with new ones in order to rebuild not only social practices but also the collective memory of certain events. The image of the “new Jew” has undergone a particular transformation, resulting from the complete denial and erasure of a large part of the cultural heritage of the diaspora.